ALCAM/CD166 is overexpressed in colorectal carcinoma and correlates with shortened patient survival. Issue 11 (27th October 2004) - Weichert, W; Knösel, T; Bellach, J; Dietel, M; Kristiansen, G
Abstract : Background: Activated leucocyte cell adhesion molecule (ALCAM) has been implicated in tumorigenesis and tumour progression of malignant melanoma and prostate cancer. Aims: To clarify the expression patterns of ALCAM in colon cancer and to correlate these with clinicopathological parameters, including patient survival. Methods: One hundred and eleven colorectal carcinomas were immunostained for ALCAM (clone MOG/07) using a standard detection system. Cytoplasmic and membranous immunoreactivity were scored semiquantitatively. Fisher's exact test, χ 2 test for trends, Kaplan–Meier analysis, and Cox's regression were applied. Results: In colorectal cancer, 58.6% and 30.6% of cases showed strong cytoplasmic and membranous expression of ALCAM, respectively. No significant correlation with patient age, tumour grade, stage, or nodal status was apparent. In survival analyses, membranous ALCAM expression correlated significantly (Cox's regression, p = 0.028; relative risk, 2.3) with shortened patient survival. Conclusions: ALCAM is frequently upregulated in colorectal cancer and is a new independent prognostic marker, underscoring the importance of ALCAM in tumour progression in this disease.